Multifunctional Immunoliposomes Enhance the Immunotherapeutic Effects of PD‐L1 Antibodies against Melanoma by Reprogramming Immunosuppressive Tumor Microenvironment. Issue 9 (16th December 2021) - Hei, Yu; Chen, Yang; Li, Qian; Mei, Zi; Pan, Jijia; Zhang, Siqi; Xiong, Chunyang; Su, Xiaodong; Wei, Shicheng
Abstract: The immunosuppressive tumor microenvironment (TME) can significantly limit the immunotherapeutic effects of the PD‐L1 antibody (aPDL1) by inhibiting the infiltration of CD8 + cytotoxic T cells (CTLs) into the tumor tissues. However, how to reprogram the immunosuppressive TME and promote the infiltration of CTLs remains a huge challenge for aPDL1 to achieve the maximum benefits. Herein, the authors design a multifunctional immunoliposome that encapsulates the adrenergic receptor blocker carvedilol (CAR) and connects the "don't eat me" signal antibody (aCD47) and aPDL1 in series via a reactive oxygen species (ROS)‐sensitive linker on the surface. In ROS‐enriched immunosuppressive TME, the multifunctional immunoliposome (CAR@aCD47/aPDL1‐SSL) can first release the outer aCD47 to block the "do not eat me" pathway, promote the phagocytosis of tumor cells by phagocytic cells, and activate CTLs. Then, the aPDL1 on the liposome surface is exposed to block the PD‐1/PD‐L1 signaling pathway, thereby inducing CTLs to kill tumor cells. CAR encapsulated in CAR@aCD47/aPDL1‐SSL can block the adrenergic nerves in the tumor tissues and reduce their densities, thereby inhibiting angiogenesis in the tumor tissues and reprogramming the immunosuppressive TME. According to the results, CAR@aCD47/aPDL1‐SSL holds an effective way to reprogram the immunosuppressive TME and significantly enhance immunotherapeutic efficiency of aPDL1 against the primary cancer and metastasis. Abstract : This research successfully develops a multifunctional immunoliposome (CAR@aCD47/aPDL1‐SSL) encapsulating an adrenergic receptor blocker CAR, connecting the "don't eat me" signal antibody (aCD47) and aPDL1 in a series via reactive oxygen species‐sensitive linkers on the surface. The CAR@aCD47/aPDL1‐SSL establishes an effective strategy for delivering antibodies and reprogramming the immunosuppressive tumor microenvironment, providing a potential way for significantly enhancing immunotherapeutic efficiency against the primary cancer and metastasis.